Applications of 3D printing in small animal magnetic resonance imaging - Nouls, John C. (J Med Imaging (Bellingham), 2019)
Three-dimensional (3D) printing has significantly impacted the quality, efficiency, and reproducibility of preclinical magnetic resonance imaging. It has vastly expanded the ability to produce MR-compatible parts that readily permit customization of animal handling, achieve consistent positioning of anatomy and RF coils promptly, and accelerate throughput. It permits the rapid and cost-effective creation of parts customized to a specific imaging study, animal species, animal weight, or even one unique animal, not routinely used in preclinical research. We illustrate the power of this technology by describing five preclinical studies and specific solutions enabled by different 3D printing processes and materials. We describe fixtures, assemblies, and devices that were created to ensure the safety of anesthetized lemurs during an MR examination of their brain or to facilitate localized, contrast-enhanced measurements of white blood cell concentration in a mouse model of pancreatitis. We illustrate expansive use of 3D printing to build a customized birdcage coil and components of a ventilator to enable imaging of pulmonary gas exchange in rats using hyperpolarized [Formula: see text]. Finally, we present applications of 3D printing to create high-quality, dual RF coils to accelerate brain connectivity mapping in mouse brain specimens and to increase the throughput of brain tumor examinations in a mouse model of pituitary adenoma.